Enhancing sense of coherence via early intervention among depressed occupational health care clients. (October 2015) - Valtonen, Mia; Raiskila, Tero; Veijola, Juha; Läksy, Kristian; Kauhanen, Marja-Liisa; Kiuttu, Jorma; Joukamaa, Matti; Hintsa, Taina; Tuulio-Henriksson, Annamari
Abstract: Background: Research on interventions improving psychological adjustment has suggested that sense of coherence (SOC) could be improved. Aims: In the present study, we measured the impact of an intervention on the SOC among adults with first-episode depression. We also examined whether rehabilitation, depression, occupational stressors, life situation stressors and socio-demographic characteristics are associated with a change in the SOC. Methods: Occupational health care clients were screened for depression using the Beck Depression Inventory (BDI) and a structured clinical interview (the The Structured Clinical Interview for DSM-IV: SCID-I). The participating subjects were randomized into a rehabilitation group ( n = 134) and control group ( n = 100) receiving treatment as usual. The Sense of Coherence Scale (SOC-13) was used at the baseline and in a 1-year follow-up to compare the change of the SOC between the groups. Results: The increase in the mean SOC score was statistically significant both in the rehabilitation group (54.91 compared with 62.85, P < 0.001) and in the control group (55.29 compared with 61.64, P < 0.001). There was no significant difference in the mean SOC scores between the groups at the follow-up. The improved SOC was associated with less severe depression ( P = 0.003) and greater decreasing in BDI ( P = 0.041) in the rehabilitation group. Conclusions: The results suggest that both rehabilitation and conventional depression treatment in a first episode of depression may enhance the SOC and that rehabilitation itself enhances the SOC more effectively among those with less severe depression or those whose BDI scores had further decreased at the 1-year follow-up.